Probing binding preferences of DNA and RNA: backbone chirality of thioacetamido-linked nucleic acids and iso-thioacetamido-linked nucleic acids to differentiate DNA versus RNA selective binding - Gokhale, Sachin S.; Gogoi, Khirud; Kumar, Vaijayanti A. (Journal of Organic Chemistry, 2010)
Subtle differences in RNA and DNA duplex geometry could be sensed by the changed stereochemistry at 3 `-amino function in the 5-atom thioacetamido linker of thioacetamido-linked nucleic acids and iso-thioacetamido-linked nucleic acids modified oligomers. In contrast to the preferred N-type sugar conformations for either 3 `- ribo- or xylo amino nucleosides, predominant S-type sugar conformations were found in the dimers. Although the CD spectral differences for the dimer blocks were found to be identical for those found in phosphodiester linked ribo/xylo dimers, the 5-atom thioactamido linker could reverse the RNA binding selectivity to DNA binding selectivity by the change in configuration at the 3 `-amino-substituted sugar.